2002
DOI: 10.1074/jbc.m106875200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Characterization of the C2 Domain of Protein Kinase Cβ

Abstract: Protein kinase C (PKC) isozymes comprise a family of related enzymes that play a central role in many intracellular eukaryotic signaling events. Isozyme specificity is mediated by association of each PKC isozyme with specific anchoring proteins, termed RACKs. The C2 domain of ␤PKC contains at least part of the RACK-binding sites. Because the C2 domain contains also a RACKlike sequence (termed pseudo-RACK), it was proposed that this pseudo-RACK site mediates intramolecular interaction with one of the RACK-bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 59 publications
(56 reference statements)
3
42
0
2
Order By: Relevance
“…The V1 domain of ⑀PKC is homologous to the C2 domain of the ␤PKC (1). However, there is an additional RACK-binding site in the V5 region of ␤PKC (38) and molecular dynamics studies with the C2 region of ␤PKC showed that an intramolecular interaction between the RACK and the RACK-binding site in the C2 region is not possible (39). Instead we suggest that the intramolecular interaction between the RACK and the RACK-binding site in ␤PKC is likely to occur between the C2 and V5 regions in ␤PKC.…”
Section: Mathematical Modeling Of ⑀Pkc Translocation Suggests That ⑀Pmentioning
confidence: 79%
“…The V1 domain of ⑀PKC is homologous to the C2 domain of the ␤PKC (1). However, there is an additional RACK-binding site in the V5 region of ␤PKC (38) and molecular dynamics studies with the C2 region of ␤PKC showed that an intramolecular interaction between the RACK and the RACK-binding site in the C2 region is not possible (39). Instead we suggest that the intramolecular interaction between the RACK and the RACK-binding site in ␤PKC is likely to occur between the C2 and V5 regions in ␤PKC.…”
Section: Mathematical Modeling Of ⑀Pkc Translocation Suggests That ⑀Pmentioning
confidence: 79%
“…In its Ca 2ϩ -bound state, this protein fold mediates an electrostatic interaction with acidic phospholipids, phosphatidylserine and phosphatidylinositol 4,5-bisphosphate (55,56), and translocates the kinase to the plasma membrane (47). In addition, Ca 2ϩ binding induces conformational changes in the regulatory domain of the kinase (47), thereby affecting its binding properties toward protein ligands (57). Therefore, our results indicate that PKC binding to filamin may be regulated by fluctuations of the local Ca 2ϩ concentration at the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…The similarity of the amino acid sequence and topology typical of polycystine-1, lipoxygenase and α-toxin enabled to unite these proteins in the PLAT-domain family that is related to the С 2 family [17,18]. Most of proteins, whose composition includes the С 2 -domain, are involved in the transduction of signals and membrane traffic including proteins that are implicated in the production of lipid secondary messengers (phospholipase А 2 , phospholipase С s , phosphatidilinositole-3-kіnase and in phosphorylation of other proteins (protein kinase С) [19][20][21]. That is the reason why LOX is referred to as "signal" enzyme that executes catalysis in the state associated with membrane structures [16,19,22].…”
Section: +mentioning
confidence: 99%